Ag AND Pd FISSION PRODUCT IMPLANTATION ON SiC LAYER IN TRISO FUEL PARTICLE OF HTGR USING SRIM/TRIM MONTE CARLO COMPUTER - Mardiyanto Mardiyanto; Abu Khalid Rivai; Nanda Shabrina (Jurnal Sains Materi Indonesia, 2022)
Ag AND Pd FISSION PRODUCT IMPLANTATION ON SiC LAYER IN TRISO FUEL PARTICLE OF HTGR USING SRIM/TRIM MONTE CARLO COMPUTER. Silicon Carbide (SiC) has excellent characteristics such as wide band gap, high electron mobility, high thermal conductivity, and radiation effects resistance. Therefore, SiC is widely used for various applications, including nuclear fuel systems. SiC is used in TRISO (Tri-Structural Isotropic) coated fuel particle in HTGR (High Temperature Gas cooled Reactor). TRISO, which consists of Inner Pyrolitic Carbon, SiC, and Outer Pyrolitic Carbon, is one of the safety systems features of the reactor. However, one of the issues of the system is corrosion of SiC caused by silver (Ag) and palladium (Pd). Nevertheless, the detailed mechanism of this corrosion phenomenon, such as the existence of Ag and Pd and how deep those two fission products penetrate the SiC layer, are still unknown. This study aims to investigate the physical interaction of Ag and Pd with the SiC coating layer of TRISO nuclear fuel particles. For this purpose, the physical effect of the penetration of the energetic Pd and Ag fission products into the SiC layer has been simulated using SRIM (Stopping and Range of Ions in Matter) /TRIM (TRansport of Ions in Matter) computer code with Monte Carlo method. Various Ag and Pd ion kinetic energies have been employed in this simulation. The results showed the Ag/SiC and Pd/SiC Ion Ranges, Doses, and Damage as the first-step evaluation to understand the corrosion phenomenon of the SiC-layer in the TRISO particles of HTGR.